Identification and quantification of cereulide in cow's milk using liquid chromatography-tandem mass spectrometry. Issue 12 (2nd December 2018) - Koike, Hiroshi; Kanda, Maki; Hayashi, Hiroshi; Matsushima, Yoko; Ohba, Yumi; Nakagawa, Yukiko; Nagano, Chieko; Sekimura, Kotaro; Hirai, Akihiko; Shindo, Tetsuya; Kamiie, Junichi; Sasamoto, Takeo; et al.
ABSTRACT: In this study, the presence of cereulide in cow's milk was identified and quantified using our validated method with liquid chromatography-tandem mass spectrometry. Cereulide was concentrated using protein acid-precipitation and extracted from the precipitate by using acetonitrile twice. The combination of protein acid-precipitation and extraction sufficiently eliminated the matrix compounds from the milk and a further clean-up step utilising solid-phase extraction could be omitted. For robustly measuring the samples and keeping the MS devices clean, the extraction solution was diluted 10-fold using methanol. Owing to the minimisation of the interferences caused by fragmentation patterns, multiple reaction monitoring information-dependent acquisition-enhanced product ion spectra enabled the characterisation and identification of cereulide. Besides the matrix effect (−4%), an external solvent calibration curve was adapted for accurate quantification. The method was validated using fortified recovery tests, at two concentrations (10 and 50 µg kg −1 ), using three samples daily on five different days based on the Japanese guidelines. This new method exhibited good accuracy ranging from 91% to 94%. The relative standard deviations of repeatability ranged from 2% to 5%, and the relative standard deviation of within-laboratory reproducibility ranged from 5% to 6%. These standard deviations satisfied the criteria for the Japanese validation guidelines. The limit of quantification (LOQ) was estimated to be 2 μg kg −1 . On the product ion spectra at the LOQ level, the library match was satisfactory with a purity fit value of >70%. The method was applied to 14 raw milk and three milk samples pasteurised using the low-temperature, long-time process and collected in Tokyo. None of the samples was found to contain the target toxin.